Effect of Dates of Transplanting on Incidence of Sucking Pests in Chilli, Capsicum annum L. - Yadav, Amit Kumar; Acharya, V. S. (International Journal of Bio-resource and Stress Management, 2018)
The experiment to examine the effect of five dates of transplanting on the incidence of major sucking pests was laid out in a randomized block design with four replications. The sowing of chilli variety RCH-1 was done at 10 days intervals in different nursery beds in landscape nursery. One month old seedlings were transplanted in the plots measuring 3.6×4.5 m2 at ten days interval starting from 15th Feb. to 27th March, 2010. The effect of five dates of transplanting, 15th Feb., 25th Feb., 7th March, 17th March and 27th March were evaluated on occurrence of major sucking pests of chilli i.e. thrips (Scirtothrips dorsalis Hood), whitefly (Bemisia tabaci Genn.), aphid (Aphis gossypii Glover), jassid (Amrasca biguttula biguttula Ishida) and mite (Polyphagotarsonemus latus Banks). The experiment on five dates of transplanting revealed that early transplanting 15th Feb. had the minimum and 27th March had maximum infestation of sucking pests viz., thrips (18.45 per three leaves and 20.30 per three leaves, respectively), whitefly (21.63 per three leaves and 29.50 per three leaves, respectively), aphid (0.43 per three leaves and 14.55 per three leaves, respectively), jassid (9.50 per three leaves and 18.63 per three leaves, respectively) and mite (2.50 per three leaves and 7.75 per three leaves, respectively). The maximum green chilli yield (24.04 q ha-1) was obtained from the crop transplanted in 15th Feb. followed by 25th Feb. (21.49 q ha-1) 7th March (19.09 q ha-1). However all these treatments were statistically at par. The minimum yield (14.19 q ha-1) was recorded in the crop transplanted on 27th March followed by the crop sown on 17th March (16.75 q ha-1).